Long-Term Impacts of Organic and Inorganic Fertilization under Soybean-based Cropping Systems on Soil Organic Carbon and Nutrients Availability in a Vertisol of Central India - Protima Rani Sarker; Dipak Ranjan Biswas; Biraj Bandhu Basak; Ranjan Bhattacharyya; Abhijit Sarkar; Debarup Das; Anchal Dass; Sunanda Biswas; Renu Singh; A.B. Singh; Ashok Kumar Patra (Journal of the Indian Society of Soil Science, 2024)
This study aims to address the long-term impacts of organic and inorganic fertilization on soil organic carbon (SOC) and available nutrients in a 17-years-old organic farming practices under soybean-based cropping systems in a Vertisol of Central India. Six fertilizer treatments consisting of organic, inorganic and their integration were followed under soybean-wheat, soybean-mustard and soybean-chickpea cropping systems. Results revealed that soybean-chickpea cropping system helped in maintaining SOC and available nutrients than other systems. This was attributed to the beneficial effects of legumes, promoting biological nitrogen fixation and improving soil conditions through microbial interactions. It was observed that treatments receiving organics either alone or integrated with inorganic fertilizer effectively enhanced the SOC content compared to the sole application of inorganic fertilizers. Among the nutrient management, integrated approaches i.e. 25% organic+75% inorganic, and 50% organic+50% inorganic, exhibited significantly elevated levels of available nutrients in soil compared to others. It can be concluded that the legumes can maintain soil quality than wheat or mustard in soybean-based cropping systems. The integration of organic and inorganic fertilizers can be a more effective nutrient management strategy for sustainable crop production compared to sole use of organic or inorganic sources.